Long-Term Functional Outcomes of Endoscopic Decompression with Destandau Technique for Lumbar Canal Stenosis - Saransh Gupta (Asian Spine Journal, 2021)
Study Design Retrospective study of patients with lumbar canal stenosis (LCS) operated using endoscopic unilateral laminotomy with bilateral decompression (ULBD). Purpose This study aimed to provide a detailed description of the technique of endoscopic decompression in LCS along with a description of the surgical anatomy and its advantages. We also discuss the clinical outcomes in patients operated using this technique. Overview of Literature In 1999, the results with the use of microscopic ULBD were published. Microscopic/microendoscopic decompression using tubular retractor system showed good to excellent results in studies that compared such techniques with midline decompression. The first description of the use of endoscope in spine surgery was in 1988 when it was used for discectomy. With advancements and familiarity with the techniques, full endoscopic surgery has found application in LCS treatment. Methods The clinical records of 953 patients who were operated between 1998 and 2008 were analyzed in 2018. Along with patient characteristics, information about return to daily activities, complication rates, and functional outcomes using Prolo score was assessed. Results L4–L5 was the most common level for which surgery was performed. Two-level decompression was performed in 116 patients; 89.5% patients were able to return to their daily activities after 2 weeks. Functional outcomes as per the Prolo score were reported by patients as excellent, good, and poor in 89.85%, 1.59%, and 8.55%, respectively. Repeat surgery was required at same level in 16 patients and at a different level in 21 patients. Total 605 patients (63.49%) were symptom-free during the 70-month follow-up, while 344 complained of residual back pain, and four complained of persistent leg pain. Conclusions ULBD using the Endospine system achieves adequate decompression in most cases and is a good alternative to open laminectomy, with the advantage of avoiding damage to the structural integrity of the spine and preserving soft tissue attachments.